PMM.63 Severe thrombocytopenia complicating pregnancy: a late diagnosis of Von Willebrands type IIb. (9th June 2014) - Scarr, C; Treharne, A; Conner, C; Rayment, R
Abstract : Aim: To understand the underlying pathology and antenatal, intrapartum and postnatal problems associated with Von Willebrand's disease, and to appreciate the importance of care planning and MDT working. Discussion: Von Willebrand's disease (VWD) is the most common inherited bleeding disorder in the general population. It is inherited in an autosomal dominant fashion and affects approximately 1% of the population. There are three subtypes with type II accounting for about 20% of cases and resulting in a qualitative defect in Von Willebrand's factor. We present the case of a primigravida lady who presented with severe thrombocytopenia (20 × 10 6 /L) unresponsive to standard medical therapy, including steroids and intravenous immunoglobulin (IVIG). We discuss the means of making such a diagnosis and the implications, both maternal and fetal. Such a bleeding diathesis in pregnancy is a major risk factor for post partum bleeding, as the normal haemostatic mechanisms are significantly impaired. We highlight the complexities of planning delivery and the importance of close cooperation with the blood transfusion services needed to ensure the safe delivery of the patient an her child. Conclusion: Von Willebrand's disease presents many fetal and maternal challenges to the management of pregnancy, delivery and puerperium. Further more, the physiological effects of pregnancy makes its presentation vary in severity and its diagnosis complex. Managing rare complex cases such as this not only requires detailed planning but also excellent inter-disciplinary team communication. Post-pregnancy contraception and future pre-pregnancy planning will be vital to her follow up.